Origami paper-based sample preconcentration using sequentially driven ion concentration polarization. Issue 5 (28th January 2021) - Lee, Junwoo; Yoo, Yong Kyoung; Lee, Dohwan; Kim, Cheonjung; Kim, Kang Hyeon; Lee, Seungmin; Kwak, Seungmin; Kang, Ji Yoon; Kim, Hyungsuk; Yoon, Dae Sung; Hur, Don; Lee, Jeong Hoon
Abstract : To overcome the hurdles of the ICP-based preconcentrator ( i.e., instability and low efficiency) under physiological conditions, we proposed a novel approach by using a sequentially driven ICP process, showing a 13-fold preconcentration factor (PF) in human serum. Abstract : Ion concentration polarization (ICP) is one of the preconcentration techniques which can acquire a high preconcentration factor. Still, the main hurdles of ICP are its instability and low efficiency under physiological conditions with high ionic strength and abundant biomolecules. Here, we suggested a sequentially driven ICP process, which enhanced the electrokinetic force required for preconcentration, enabling enrichment of highly ionic raw samples without increasing the electric field. We acquired a 13-fold preconcentration factor (PF) in human serum using a paper-based origami structure consisting of multiple layers for three-dimensional sequential ICP (3D seq-ICP). Moreover, we demonstrated a paper-based enzyme-linked immunosorbent assay (ELISA) by 3D seq-ICP using tau protein, showing a 6-fold increase in ELISA signals.